Effect of fruit maturation and ripening potential for optimum eating quality of 'Forelle' pears - Carmichael, Patricia Cassie (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Horticulture))--University of Stellenbosch, 2011.